Pengaruh persepsi nilai terhadap kepuasan nasabah tabungan Bank X di Bandung - Yati Yulianty; Reinantha Yaputra (Jurnal Manajemen Maranatha, 2019)
Customer satisfaction is important in the continuity of banking services business, especially faced of the market competition today. Value obtained by customers based on experience is expected to create satisfaction, therefore this research is conducted with the aim of seeing the influence of value perception on customer satisfaction of Savings Bank X in Bandung, which is the perception of value consist of 3 aspects that is functional value, emotional value, and social value. Research method used through explanation survey with descriptive approach associative. The sample used was 53 respondents with purposive sampling technique. Data collection through questionnaires is then performed statistical data analysis techniques with multiple linear regressions, through F test and t test to test the hypothesis. The result of the research shows that the positive influence of functional value on customer satisfaction can not be confirmed. The positive influence of emotional value on customer satisfaction can not be confirmed. The positive influence of social values on customer satisfaction can be confirmed. Overall value perception has a positive influence on satisfaction.